Invasive Hemodynamic Monitoring and Arterial Blood Gas Exchange During Spinal vs General Anesthesia for Cesarean Delivery in Mongolian Parturient - Banzar, Mungun; Jamsranjav, Enkhtsetseg; Janlav, Munkhtsetseg; Lundeg, Ganbold (Central Asian Journal of Medical Sciences, 2024)
Objective: This study investigated the accuracy and precision of continuous, invasive blood pressure obtained using the arterial line system in patients undergoing cesarean section with spinal and general anesthesia. Methods: A total of 150 parturient women who underwent C-sections from July 1, 2021, to Dec 30, 2023, were divided into two groups: the GA (general anesthesia) group (n=50) and the SA (spinal anesthesia) group (n=100). In this prospective observational study, we measured and compared the changes in hemodynamic fluctuation and arterial blood gas deviations under C-section with either spinal or general anesthesia. Results: One hundred fifty patients were recruited for the study after exclusions, and data were analyzed for 150 patients. There were no significant differences in the time from anesthesia to incision, the operation duration, infused crystalloid volume, blood loss, and urine output. The most frequent complications were surgery hypotension, tachycardia, nausea, and headache in the SA group, and tachycardia, hypertension, in the GA group These complications may cause SA’s impact on the sympathetic nerves, resulting in dilated blood vessels and reflex tachycardia. Conclusion: It has been suggested that the choice of anesthesia technique has a significant impact on hemodynamic stability during cesarean section.